2013
DOI: 10.1016/j.comnet.2012.12.016
|View full text |Cite
|
Sign up to set email alerts
|

BitTorrent-like P2P approaches for VoD: A comparative study

Abstract: The enormous popularity of Video on Demand (VoD) has attracted substantial research attention into the effective use of peer-to-peer (P2P) architectures to provide solutions at large-scale. In particular, the high efficiency of BitTorrent has inspired many P2P protocols for VoD. However, these protocols use different approaches to adapt the design of Bittorrent to VoD, and in most cases their performance has been evaluated separately and in limited scenarios. As a consequence, the research community still lack… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
35
0
7

Year Published

2015
2015
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(43 citation statements)
references
References 35 publications
1
35
0
7
Order By: Relevance
“…So we adapt its design to satisfy the fundamental quality-of-service requirements for streaming, while still maintaining the high efficiency of the original BT protocol. Based on [13], we design an adaptive double window mechanism for piece selection, considering the urgency and scarcity of pieces. There are two windows in the video file, emergency window and normal window.…”
Section: System Modelmentioning
confidence: 99%
“…So we adapt its design to satisfy the fundamental quality-of-service requirements for streaming, while still maintaining the high efficiency of the original BT protocol. Based on [13], we design an adaptive double window mechanism for piece selection, considering the urgency and scarcity of pieces. There are two windows in the video file, emergency window and normal window.…”
Section: System Modelmentioning
confidence: 99%
“…D'Acunto et al [9] analyzed P2P applications and found that 88% of the participants in the studied P2P network were behind NATs. Sherry et al [3] obtained configurations from 57 enterprise networks and revealed that they can contain as many middleboxes as routers.…”
Section: Introductionmentioning
confidence: 99%
“…Plenty of practical P2P approaches, like the BitTorrent protocol [6], have been successful in the past years. In fact, the great efficiency achieved by BitTorrent for the distribution of large amounts of data inspired its adoption for on-demand video streaming [7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…Plenty of practical P2P approaches, like the BitTorrent protocol [6], have been successful in the past years. In fact, the great efficiency achieved by BitTorrent for the distribution of large amounts of data inspired its adoption for on-demand video streaming [7][8][9].Peer-Selection Policy is the term assigned to one of the core concepts of BitTorrent. By stimulating direct reciprocity and cooperation, its design specifies who makes use of the uplink capacity from all the peers inside the swarm (i.e., a group of peers downloading a same content).…”
mentioning
confidence: 99%
See 1 more Smart Citation